Engraved gems as part of the Augustan propaganda. Some examples from Croatia - Kaić, Iva (Array, 2014)
Engraved gems in the time of Augustus were used as means of propaganda, with diverse and well-known motifs that can be linked to such a political program. Glyptic collections which are kept in Croatian museums are not fully published. However, among the published material, some engraved gems that belong to this group can be singled out, such as gems depicting capricorn, a zodiac sign of Augustus, or a famous glass cameo with Livia's bust.